Alaska : Wild and Free - Harris, Nic (New York Cambridge Discovery, 2014)
Alaska is one of the most beautiful places on Earth. It s also one of the most dangerous. Mountains, bears, glaciers, and dog sledding: explore the natural beauty and unique way of life in this US state.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Elementary level